When in Rome: the exercise of power by foreign multinational companies in the United States1. (May 2014) - Compa, Lance
Multinational corporations exercise power in the United States by integrating themselves into the US economic and legal systems, not by interfering with them. Firms take advantage of the relatively deregulated labour market in the United States and its 'at-will' employment relations, compared with 'just cause' requirements elsewhere. Many multinational companies also adopt US management-style behaviour towards trade unions, notwithstanding their publicly declared support for global norms on workers' freedom of association. They exploit US labour laws that violate international standards and interfere with trade union formation. Case studies examine several examples of this 'when in Rome' anti-union phenomenon. At the same time, some counter-examples of companies that adhere to ILO core standards are offered. The conclusion contains recommendations for securing multinational companies' respect for workers' freedom of association in the United States, including application of ILO core standards, UN Guiding Principles, OECD Guidelines and Global Framework Agreements.